Tеchologies of the distance studies of pediatricians - L. M. Boiarskaia; О. А. Ryzhov; Yu. V. Kotlova (Zaporozhye State Medical University, 2014)
The experience of the thematic improvement courses for pediatricians, family doctors in ZSMU proves that distance education should be based on the technology of high professional informative, interactive learning, have the competence and cognitive vector.